IMPLEMENTATION OF PERSONNEL SERVICE INNOVATION IN REGIONAL OFFICE IX JAYAPURA STATE PERSONNEL AGENCY (Journal of Pharmaceutical Negative Results, 2023)
The purpose of this research is to examine the implementation of the Civil Service Notification Information System (SINOKEN) application innovation and what are the supporting and inhibiting factors for the implementation of the Civil Service Notification Information System (SINOKEN) application innovation at Regional Office IX of Jayapura State Personnel Agency. The research method used is a qualitative approach. Qualitative approach because the object under study is the implementation of a policy related to human work processes. Data were collected from interviews with informants and through literature studies relevant to this research. The results of the study show that the implementation of the SINOKEN application using George C. Edward's top-down policy models can be influenced by 4 main factors, namely: communication, Source, Disposition or Attitudes, and Bureaucratic structures. bureaucracy) run effectively. As for the supporting factors for the implementation of SINOKEN, there is a circular letter issued by Regional Office IX State Civil Service Agency (BKN) Jayapura and the support of related institutions. The inhibiting factors in the implementation of SINOKEN are the area and geographical conditions of Papua which are the main causes of uneven access to the internet network and the frequent occurrence of employee mutations.